Language and Space : an international handbook of linguistic variation. - Hinskens, Frans, 1956-; Taeldeman, Johan, 1943-2017 (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2013)
This handbook aims at a state-of-the-art overview of earlier and recent research into older, newer and emerging non-standard varieties, transplanted varieties and daughter languages of Dutch. The discussion concerns the theoretical embedding, interdisciplinary connections and the methodology of the studies at issue. It presents general concepts and approaches in the broad domain of Dutch variation linguistics and the main developments.